Predominance of extensively-drug resistant Acinetobacter baumannii carrying bla OXA-23 in Jordanian patients admitted to the intensive care units - Qutaiba Ababneh; Neda’a Aldaken; Ziad Jaradat; Ekhlas Al-Rousan; Zeina Inaya; Dua’a Alsaleh; Dua’a Alawneh; Sara Al Sbei; Ismail Saadoun (PLoS ONE, 2025)
Background and Aim The global emergence of Acinetobacter baumannii is of great concern, especially inside intensive care units (ICUs). This study investigated the prevalence, antibiotic resistance, biofilm formation and genetic relatedness of A. baumannii recovered from ICU patients in three major hospitals in Jordan. Methods The A. baumannii isolates included in this study were identified by the detection of the blaOXA-51 gene, and a multiplex PCR assay. Antibiotic susceptibility testing was performed using the disk diffusion and broth microdilution methods, and the ability of the isolates to form biofilms was tested using the 96-well plate assay. All isolates were tested for the presence of carbapenemases-encoding genes by PCR. Clonal relatedness was assessed by Rep-PCR and dendrogram analysis. Results Overall, 148 A. baumannii isolates were identified, with 96.7% of the isolates recognized as carbapenem resistant A. baumannii. Based on their resistance patterns, 90% of the isolates were extensively resistant (XDR). The highest prevalence of carbapenemases-encoding genes was for blaOXA-23-like (96.7%), followed by blaADC (93.9.2%), blaVIM (56.8%) and blaNDM-1 (7.4%). Almost 80% of the isolates were able to form biofilms, with 63.2% classified as strong biofilm former. Rep-PCR and clustering analysis revealed 26 different clusters and the circulation of hospital-specific clones. Conclusions Our study revealed an alarming high prevalence of XDR, blaOXA-23-carrying and strong biofilm-producing A. baumannii among ICU patients. These findings call for continuous epidemiological surveillance and implementation of prevention strategies to reduce infections and dissemination of such a problematic pathogen inside the ICUs.